W1 Establishing a simulation faculty development course – sharing the experience. (5th November 2017) - Calthorpe, Nicola
Abstract : Background: Context and Aims During a 12 month secondment with HEE we established a 2 day Simulation Faculty Train the Trainers course called HEDSup (Healthcare Educators Development for Simulation). We delivered the course to 85 multidisciplinary candidates over 6 courses and would like to share the lessons learnt, experiences gained and pitfalls to avoid with colleagues who are looking to deliver faculty development courses. Our curriculum utilized a blended learning approach with a focus on the educational theory of simulation, the role of human factors and non technical skills in simulation teaching, debriefing models and techniques, debriefing the debrief and how to argue the case for simulation. We developed pre course learning materials, scenario design templates, videos to practice debriefing with, debriefing the debrief skills, process mapping delivering a simulation programme and an online feedback tool. The aim of the workshop would be to share our experience and those of the workshop participants and process map the delivery of a faculty development programme sending attendees away with the ideas, resolve and enthusiasm to deliver a high quality faculty development course. Learning Objectives and Session Description: The learning objectives would be: Gain insight into the lessons learnt by ourselves and other delegates in establishing faculty development courses Share the knowledge of educational methods which can be used in delivering faculty development courses Process map establishing a faculty development course Generate the enthusiasm for delegates to deliver their course The session would consist of Introduction to the structure of our course and how we went about establishing it Group discussion of lessons learnt by delegates who have also established faculty development programmes Group exercise of delegates process mapping the delivery of a faculty development programme from inception through to course delivery and review. Educational Methods: The educational methods used would be group discussions, a process mapping exercise, and review of the results gained and take home messages. Target Audience, Maximum Number of Participants: The target audience would be delegates who are able to share their own experiences, and others who wish to develop their own faculty development programmes.